High resolution NMR spectroscopy : understanding molecules and their electronic structures - Contreras, Ruben H. (Science and technology of atomic, molecular, condensed matter & biological systems, 2013)
The progress in Nuclear Magnetic Resonance (NMR) spectroscopy that took place during the last several decades is observed in both experimental capabilities and theoretical approaches to study the spectral parameters. The scope of NMR spectroscopy for studying a large series of molecular problems has notably broadened. However, at the same time, it requires specialists to fully use its potentialities. This is a notorious problem and it is reflected in the current literature where this spectroscopy is often only used in a routine way. Also, it is seldom used in several disciplines where it co.